Observation of maximum injection upper limit for energetic proton events according to SOHO/ERNE measurements - Allawi, H.; Al-Ramdhan, W.; Al-Sawad, A. (Advances in Astronomy and Space Physics, 2011)
We analyzed 25 solar energetic particle events, with energies ∼ 1 − 100 MeV, observed with ERNE instrument onboard Solar and Heliospheric Observatory (SOHO) and found that all of the solar energetic particlse were associated with coronal mass ejections, observed with LASCO/SOHO. The observational data suggests that the associated coronal mass ejections were located at lower heliocentric altitudes during the time of maximum intensity of the high energy protons than those during the time of maximum intensity of lower energy protons. This might indicate that the upper limit of maximum acceleration by the shock waves decreases earlier as we go higher in the proton energy level.